Whose truth did prevail? an analysis of the daily broadsheets, The Philippine Star, in the context of MVP (Manny V. Pangilinan) group’s acquisition. - Tubije, Rogelio II Bustamante; Khan, Rachel E. Ph. D (Quezon City College of Mass Communication, University of the Philippines, Diliman, 2018)
The MVP (Manny Pangilinan) Group of Companies is among the country's top conglomerates, with substantial holdings across diverse strategic fields such as telecommunications, infrastructure, water and power distribution, mining and healthcare. Yet what makes the MVP Group so powerful is its acquisition of various media outlets, ranging from TV, radio to print media. This includes the Philippine Star - one of the country's top broadsheets. With the new ownership, Star was caught in a dilemma. Its parent conglomerate subsidiaries have been subject to controversies like overpricing and substandard services. Thus, it is important to determine if such corporate orientation runs afoul to the press's primary duty as watchdog of society.

This study examines Star's content in relation to MPV's perceived economic interest. It also examines how change in ownership influenced story content, advertising pattern, and story angles on MVP-owned public utilities. Quantitative-qualitative content analyses and interviews were utilized to achieve the objective.

Star's subsequent shift in its treatment of MVP-related stories concurrent with the revamp in the publication's ownership affirms the Propaganda Model of Communication which identifies media ownership as the primary filter of media content. Post-acquisition, Star's gatekeeper's put forth MVP Groups' corporate agenda by consistently highlighting stories favorable to MVP's subsidiaries, downplaying negative publicities, and blurring the distinction between promotional materials and objective news reports.
Thesis (A.B. Journalism)
Keywords: Mass media -- Objectivity; Mass media and propaganda -- Philippines; Mass media and business -- Philippines